MENINGKATKAN KETERAMPILAN PROSES SAINS DAN PEMAHAMAN KONSEP ELASTISITAS SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK - Latudeng, Emntekiu; Anas, Muhammad; Hamimu, La (-)
The aims of this study were: 1) to analyze the significance of difference between average gain of students’ science process skill who learn with project based learning and those who learn with conventional learning, and 2) to analyze the significance of difference between average gain of students’ understanding on elasticity who learn with project based learning and those who learn with conventional learning. This study was a quasi experiment research with nonequivalent control group design. The population of this study was XI IPA students at SMA Negeri 10 Kendari consisted of 77 students, were distributed in 3 parallel groups. The sample of this study was students of XI IPA 2 and XI IPA 3 consisted of 51 students. The data obtained were analyzed by compare means with independent-sample t-test. The result showed that: 1) there was significant difference between average gain of students’ science process skill who learn with project based learning and those who learn with conventional learning, and 2) there was significant difference between average gain of students’ understanding on elasticity who learn with project based learning and those who learn with conventional learning. Thereby, project based learning had significant effect on students’ science process skill and understanding on elasticity.Keywords:   project based learning, science process skill, understanding on elasticity.